14K prolactin derived 14‐mer antiangiogenic peptide targets bradykinin‐/nitric oxide‐cGMP‐dependent angiogenesis - Jaeok Lee; Pavitra Kumar; Suganya Natarajan; So Hyeon Park; Syamantak Majumder; Lakshmikirupa Sundaresan; Kambadur Muralidhar; Jong‐Soon Choi; Hwa Jeong Lee; Suvro Chatterjee (FEBS Open Bio)
Over the past few decades, VEGF‐targeted antiangiogenic therapy for cancers has gained increasing attention. Nevertheless, there are still several limitations such as the potential resistance mechanisms arising in cancer cells against these therapies and their potential adverse effects. These limitations highlight the need for novel anti‐angiogenesis molecules and better understanding of the mechanisms of tumor angiogenesis. In the present study, we investigated the antiangiogenic properties of a novel 14‐mer antiangiogenic peptide (14‐MAP) derived from N‐terminal 14 kDa buffalo prolactin and characterized its mode of action. 14‐MAP at the picomolar concentration inhibited VEGF‐ and bradykinin (an autacoid peptide expressed in vascular tissues in pathophysiology, BK)‐stimulated endothelial nitric oxide (eNO) production, cell migration, and proliferation in endothelial cells and vessel development in the chick embryo. Although this peptide inhibited both VEGF‐ and BK‐dependent angiogenic processes, its action was more pronounced in the latter. Moreover, the interference of 14‐MAP with the eNO synthase (eNOS)‐cyclic GMP pathway was also identified. A combination of a low dose of Avastin, a widely used drug targeting VEGF‐dependent angiogenesis, and 14‐MAP significantly reduced tumor size in an in vivo model of human colon cancer. Taken together, our results suggest that 14‐MAP, a BK‐ and eNOS‐dependent antiangiogenic peptide, might be useful for overcoming the limitation of VEGF‐targeted antiangiogenic therapy in cancer patients. However, further studies will be required to further characterize its mode of action and therapeutic potential.